Implementation of SDGs 11 and LEZ Policy toward Visitor Satisfaction in Kota Tua Area Jakarta - Istanto, Ismayanti; Djamhur, Ina; Sapitriyadi, Irwanto (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Sustainable tourism can be achieved by executing the action of SDGS 11 Sustainable Cities and Communities. The Low Emission Zone (LEZ) policy is a translation of SDGS 11 implemented in cities worldwide. In 2021, the Special Capital Region Government of Jakarta chose Kota Tua Area Jakarta (KTA) as LEZ pilot project area to try out a form of restriction of motorized vehicles in an area in many ways. However, as LEZ policy was executed, visitor reviews were still unknown. This research aimed to evaluate SDGS 11 and LEZ implementation in KTA and weigh the contribution toward tourist satisfaction. A descriptive quantitative study from November 2022 until January 2023 was taken using primary data from 100 questionnaires used on a purposive sample of tourist aged over 18 who was repeat visitor of KTA. The data analysis used the explanatory method, multi-regression, Pearson Correlation Product Moment, and determinant coefficient analysis. The result showed that the implementation of SDGS 11 in KTA was compatible with the target of SDG Goal 11. LEZ policy has been very well executed. Visitors claimed they were strongly satisfied with tourist spots in KTA. Implementation of SDGS 11 and LEZ policy simultaneously and partially influenced visitor satisfaction. The SDGS 11 and LEZ policy in KTA contributed 23.4 percent to tourist satisfaction, and the remaining 76.6 percent was supported by other factors. It is recommended to pay attention to the safety aspect of KTA, organize parking, and increase the quality of tourist facilities.